Impact of Intravenous Fish Oil Lipid Emulsion on Short-Term Postoperative Outcomes in Rectal Cancer Patients Following Neoadjuvant Therapy: A Propensity Score-Matched Study - Yang L; Pi F; Wei Z; Peng X (Cancer Management and Research)
Liping Yang, Feng Pi, Zhengqiang Wei, Xudong Peng Department of Gastrointestinal Surgery, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Xudong Peng, The First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi Road, Yuanjiagang, Yuzhong District, Chongqing, People’s Republic of China, Tel +862389011014, Email 846393577@qq.comPurpose: Previous studies lack a consensus on the role of fish oil lipid emulsion in postoperative complications and recovery in rectal cancer patients post-neoadjuvant therapy. This study aimed to evaluate the impact of intravenous fish oil lipid emulsion on short-term clinical outcomes in these patients.Patients and Methods: This retrospective study included patients who underwent radical surgery for RC after NT between November 2018 and April 2022. Patients were divided into two groups: the fish oil group (receiving fish oil treatment) and the control group (not receiving fish oil treatment). Propensity Score Matching was used to analyze and compare postoperative complications and other relevant clinical indicators between the two groups. A total of 208 patients were included, with 33 patients in each group after PSM.Results: The results showed no significant differences between the two groups in terms of time to first flatus, time to first defecation, or time to first liquid diet intake (p > 0.05). However, compared to the control group, the fish oil group had significantly lower rates of postoperative complications, shorter hospital stays, and earlier tolerance to solid food (p < 0.05). Additionally, the fish oil group effectively suppressed the decline in postoperative albumin levels (p < 0.05).Conclusion: These findings suggest that perioperative intravenous supplementation of fish oil may effectively reduce postoperative complications, accelerate recovery, and improve postoperative nutritional status in rectal cancer patients post-neoadjuvant therapy.Keywords: postoperative complications, nutritional status, gastrointestinal recovery, propensity score matching, omega-3 polyunsaturated fatty acids, colorectal cancer